Problematika Formalisasi Pemberiakuan Syariat Islam dalam Konteks Ketatanegaraan Indonesia - muntoha muntoha (Fakultas Hukum Universitas Islam Indonesia, 2001)
Indiscussing about how too vercome some obstructions of law enforcement the Islamic law fonnalization as an integrated partofpositive law should be noted here seriously. Unfortunately, the strategic collision between the substantive and the formalism mainstream and the various schools havebeen bearing a problematic issue. Despite the fact of this problematic case, the national law building would require an integrated arrangement for law enforcement and lawmaking process which meets rhe socialneeds ofjustice.